Characterization of Cimetidine–Piroxicam Coprecipitate Interaction Using Experimental Studies and Molecular Dynamic Simulations - Tantishaiyakul, Vimon (Springer US, 2010)
The crystalline states of cimetidine and piroxicam, when coprecipitated from solvents containing 1:1 mole ratio, were transformed to amorphous states as observed using powder X-ray diffraction (PXRD). Amorphous forms of drugs generally exhibit higher water solubility than crystalline forms. It is therefore interesting to investigate the interactions that cause the transformation of both the crystalline drugs. Intermolecular interactions between the drugs were determined using Fourier-transform infrared spectroscopy (FTIR) and solid-state (13)C CP/MAS NMR. Molecular dynamic (MD) simulation was performed for the first time for this type of study to indicate the specific groups involved in the interactions based on radial distribution function (RDF) analyses. RDF is a useful tool to describe the average density of atoms at a distance from a specified atom. FTIR spectra revealed a shift of the C≡N stretching band of cimetidine. The (13)C CP/MAS NMR spectra indicated downfield shifts of C(11), C(15) and C(7) of piroxicam. RDF analyses indicated that intermolecular interactions occurred between the amide oxygen atom as well as the pyridyl nitrogen of piroxicam and H-N(3) of cimetidine. The hydrogen atom (O–H) at C(7) interacts with the N(1) of cimetidine. Since the MD simulation results are consistent with, and complementary to the experimental analyses, such simulations could provide a novel strategy for investigating specific interacting groups of drugs in coprecipitates, or in amorphous mixtures.